2015
DOI: 10.1539/joh.13-0284-oa
|View full text |Cite
|
Sign up to set email alerts
|

The association between rotating shift work and increased occupational stress in nurses

Abstract: -Purpose: The aim of this study was to investigate whether rotating shift work increases occupational stress in nurses. Methods: This study measured shift work scheduling and occupational stress by using the Effort-Reward Imbalance model with selfreported questionnaires in a sample of 654 female nurses. Results: Overcommitment risk was higher in nurses who worked rotating shifts than in those who worked day/non-night shifts (OR, 2.16; 95% CI, 1.03−4.66). However, an effort/reward imbalance was not directly ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 27 publications
3
50
0
4
Order By: Relevance
“…() did not find a difference in job stress according to the type of shift worked, but in a later study by the same authors they found that rotating shifts were associated with effort‐reward imbalance (Lin et al . ). In the study by Hoffman and Scott (), nurses working 12‐hour shifts reported greater levels of stress than those working 8‐hour shifts.…”
Section: Resultsmentioning
confidence: 97%
“…() did not find a difference in job stress according to the type of shift worked, but in a later study by the same authors they found that rotating shifts were associated with effort‐reward imbalance (Lin et al . ). In the study by Hoffman and Scott (), nurses working 12‐hour shifts reported greater levels of stress than those working 8‐hour shifts.…”
Section: Resultsmentioning
confidence: 97%
“…The present findings suggested that restorative yoga could be a self‐care method for alleviating psychological and physical stress reactions. However, it should be considered that the score for “psychological and physical reactions” would not only be influenced by restorative yoga, but also by job stressors such as the frequency of shift changes, cumulative night shift days, days off after the last night shift, and weekly overtime, and would also be influenced by social support at work . Although "job stressors" and "social support at work" were not investigated in this study, the influence of these factors on “psychological and physical stress reactions” should be evaluated.…”
Section: Discussionmentioning
confidence: 97%
“…Nurses may develop physical and psychological problems such as anxiety or depression due to occupational stress . It has been reported that nurses who work rotating shifts are more likely to experience work‐related stress, so implementing programs and strategies to eliminate stressful working conditions in hospitals is critical for prevention and alleviation of work stress among nurses . Previous studies have demonstrated the efficacy of yoga for improving self‐care and reducing burnout among nurses, as well as potential benefits of yoga for reducing stress and muscle tension or improving self‐care in nurses .…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have reported that shift work is associated with greater work stress 50. However, little is known about what specific components of non-standard schedules may be contributing to this significant relationship.…”
Section: Discussionmentioning
confidence: 99%